2013
DOI: 10.2174/1574886311308010008
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Drug Safety and Clinical Databases

Abstract: Clinical and drugs safety organisations run their operation independently and use separate databases designed to comply with different data standards. This separation is neither efficient nor effective since investigators need to report serious adverse events both to the clinical and drug safety departments, causing the respective databases to contain partially overlapping data sets containing common elements that need to be reconciled. Electronic data capture provides the opportunity to avoid duplicate storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Publicizing existing internal data and/or funding of prospective studies to investigate how DOAC-specific laboratory tests correlate to clinical adverse events would provide useful clinical guidance. As such collaboration between these agencies and academia is called upon and can promote efficient and expansive research toward drug-drug interactions [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Publicizing existing internal data and/or funding of prospective studies to investigate how DOAC-specific laboratory tests correlate to clinical adverse events would provide useful clinical guidance. As such collaboration between these agencies and academia is called upon and can promote efficient and expansive research toward drug-drug interactions [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, it has been suggested that development of these technologies suffers from the lack of a clear national direction towards unifying clinical and medical data, with no common format for all data systems. Not only would EDC benefit clinical research, but pharmacovigilance and drug safety regulation could also be improved .…”
Section: Resultsmentioning
confidence: 99%
“…Once EDC systems are implemented, separate subdatabases can be retained to meet independent reporting requirements. However, a single aggregate database jointly shared by the clinical and drug safety departments is essential to advancing pharmacovigilance [12]. In practice, the idea is that once keyed in through EDC, all the safety information that is currently separately directed and stored in the clinical and safety database is stored in one single repository.…”
Section: A Unified Database Will Drive Improved Data Capturementioning
confidence: 99%